Helicobacter pylori infection in Turkish children with gastrointestinal symptoms and evaluation of serology - Sökücü, Semra; Süoğlu, Özlem D.; Türkkan, Emine; Elkabes, Berna; Özden, Tülin; Saner, Günay (The Turkish Journal of Pediatrics, 2002)
Helicobacter pylori infection is a common etiopathogenetic factor in children with gastrointestinal symptoms in the developing world. Although serology offers an easy noninvasive method of diagnosis, its sensitivity and specificity are reported to be low among children. In this prospective study, we investigated the frequency and endoscopical and morphological findings of H. pylori infection in 180 Turkish children who underwent upper gastrointestinal endoscopy either for peptic symptoms or on a routine basis and in asymptomatic pediatric patients who underwent endoscopy for other reasons, and then evaluated the diagnostic accuracy of serology in our population. Overall H. pylori infection was diagnosed in 77 of the 180 patients (42.7%) by histology and urease test. The sensitivity of H. pylori specific IgG antibody assay by ELISA was determined to be 100%, while the specificity was 98%, the positive predictive value 97.4%, the negative predictive value 100%. Frequency of H. pylori infection is high in Turkish pediatric patients without gastrointestinal symptoms as well as in children with gastrointestinal complaints. H. pylori specific antibody assay is a noninvasive and sensitive method for the diagnosis of H. pylori infection in the Turkish pediatric population.